Aquaphonics system for a clarias batrachus wastewater treatment - Nurul Ain, Abu Othman (2014)
The increasing pollution of water resources in Malaysia over the past few years is being concern. If water is • not properly maintained from now, the country would lose our water resources by 2020. As example, the water crisis in Selangor began to occur as a result of the quantity of Water that reaches the standard class 1, 2 and 2b, which currently only less than-25 percent of the total 142.38 miles. This shows that only 49 miles of river in Selangor are suitable to be treated due to the total water quality that meets the highest standards of clean drinking water. The purpose of this study was to determine the wastewater characteristics such as pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and Ammonium Nitrogen (NI-h--N), to determine the effect of 0, 2, 4 and 6 hours of hydraulic retention time (HIRT) treatment on wastewater quality and to determine the growth of adopted vegetable during treatment. Aquaphonics system is used to treat wastewater from catfish (Clarias Batrachus). This aquaphonics system provides many benefits to our environment and society. Among the advantages of this aquaphonics system are it can preserve and protecting our environment from pollution, contribute to the society in preventing the community from any harm and danger of chemicals and can reduce cost life since this aquaphonics system can producing fish and vegetable that are free from chemical. Aquaphonics system allows us to replace traditional agriculture where a used fertilizer, which is contains many, chemicals. Water resources pollution which is particularly rivers and lakes in Malaysia can be reduced. The results showed that the pH value is at a safe level of 6.5 - 7.5 throughout the study. It can be concluded that the pH can be controlled depending on the rate of the wastewater temperature in the aquarium and the reaction between the unclean fish and vegetables. The value of BOD, COD and NH3 -N also increase in first three weeks of study. The value o all parameter was decrease where the BOD value from 41.7 mg/L to 33.5 mg/L, the COD value also from 203 mg/L to 102 mg/L, the TSS value from 148 mg/L to 29 mgIL and the NH3-N value from 2.53 mg/L to 1.29 mg/L. The value of this all parameters decreases and become better start at the fourth week of the study. The growth mustard (brasica fuller var chinensis) showed a decline in the early stages but got better start in week four. This is because some mustard dies due to the un-ability to hold water when conducting the testing of effect of hydraulic retention time (HRT). The collected data can be applied and restored to make the better results and outcome in future. This data can be used in our agricultural sector.